The design and implementation of web-based multimedia learning content management system for arabic vocabulary pronunciation / Mohd Nizam Osman ... [et al.] - Osman, Mohd Nizam; Maghribi, Mushahadah; Sarif Puddin, Nur Shazlena; Sedek, Khairul Anwar; Othman, Nor Arzami (UiTM Cawangan Perlis, 2022)
Arabic vocabulary is one of the important knowledge areas in learning Arabic language. In fact, that in the current world, almost 80% of Muslim are non-native speaker of Arabic language. Some people found that Arabic vocabulary is difficult and confusing to learn and subsequently failed to master the knowledge. Besides, most of the higher education in Malaysia has been introduce Arabic subject in their curriculum or plan of study. On the other hand, learners faced difficulties in learning Arabic vocabulary, especially the pronunciation due to limited hours of learning in the class and less attractive of teaching materials. The purpose of this study is to design and develop a web-based multimedia learning content management system (LCMS) to enhance the learning of Arabic vocabulary pronunciation. The proposed system was developed using Articulate Storyline for implementing interactive learning which all multimedia elements can be blended in the system. The development process follows the System Development Life Cycle (SDLC) as a methodology. Then, the proposed system is evaluated using expert reviews by distributing questionnaires among five expert users, and User Acceptance Test (UAT) contributed thirty respondents to determine the effectiveness of the system. The result from the Expert Review shows that the proposed system is suitable to use but still needs some improvements. While the result from the UAT indicates that the proposed system has a positive impact and to be well accepted by the majority of the users. Therefore, the most significant potential is the ability of the proposed system to help, assist, enhance and enrich the experience of learning Arabic vocabulary pronunciation more effective and efficient.